A Brief Review on Murraya paniculata (Orange Jasmine): pharmacognosy, phytochemistry and ethanomedicinal uses - Deepa Joshi; Kashmira J. Gohil (Korean Pharmacopuncture Institute, 2023)
Objectives: Murraya paniculata (family-Rutaceae), popularly known as orange jasmine, is the most important evergreen plant. The Rutaceae family is economically significant due to its diverse edible fruits and essential oils.Methods : : Murraya paniculata extracts (MPE) of leaf have been shown to include phenolic compounds, highly oxygenated flavonoids, flavanones, sesquiterpenoids, polymethoxy glycosides, and coumarins. Cyclocitral, methyl salicylate, trans-nerolidol, cubenol, isogermacrene, -cadinol, and cubeb-11-ene are all abundant in MPE. The usages of various parts of this plant, such as bark, leaves and flower, as a remedy for a variety of ailments as widely recorded in the traditional literature. The plant has anti-diabetic, anti-obesity, antibacterial, anti-implantation, anti-oxidative, cytotoxic, anti-diarrheal, antidepressant and anti-anxiety properties and many others.Results : : The goal of the review is to reignite interest in this potential plant, encouraging researchers to continue their research in order to uncover novel therapeutic compounds for the treatment and management of a range of infections. The current review provided a comprehensive overview of this traditional unique plant.Conclusion : : The review paves a way for exploring its active chemical elements with substantial pharmacological values further for potential benefits of mankind.